"Religion" is complex and diverse. Issue 4 (2nd October 2017) - Watts, Fraser; Bretherton, Roger
ABSTRACT: Religion is a multi-faceted phenomenon including cognition, behavior, experience and more. It is also very diverse; there are many different forms of religion, depending on evolutionary context, culture, personality and so on. In view of this it is misleading to make claims about anything as broad and general as "religion", without specifying what kind of religion is under the spotlight. There is a danger of erroneous extrapolation from one specific form of religion to religion in general. Another danger is of studying such mixed and diverse forms of religion that there is little prospect of discovering anything that they all have in common. Though there is much that is commendable in these Hilbert papers, their most conspicuous weakness is the tendency to over-generalize about religion.